Interspecific differences in male vocalizations of three sympatric fur seals (Arctocephalus spp.) - Page, BC; Goldsworthy, SD; Mark Hindell; Mckenzie, J (2002)
This study investigated species recognition based on bark calls and full threat calls (FTCs) in three fur seal species, Antarctic Arctocephalus gazella, subantarctic A. tropicalis and New Zealand A. forsteri, that breed sympatrically and hybridize at subantarctic Macquarie Island. Bark calls, which are produced by males in male-female interactions, were more species-specific than their full threat calls, suggesting that bark calls could be used in species recognition and female mate choice. Further, the bark calls of A. tropicalis were more species-specific than those of A. gazella and A. forsteri, suggesting that divergence of calls between species is a consequence of phylogenetic distance, or has resulted from sexual selection through female mate choice. We believe the latter is more probable as we did not observe similar divergence in the FTCs of males. As such, the highly divergent bark calls of A. tropicalis may have resulted from sexual selection that has promoted pre-mating isolation via the process of reinforcement.